SENYAWA KIMIA STEROL DARI KULTUR JARINGAN KELADI TIKUS (Typhonium divaricatum Decne) - Lilik Sulastri; Partomuan Simanjuntak (Jurnal Ilmiah Manuntung, 2019)
Keladi tikus (Typhonium divaricatum Decne) is one of Aracaceae family which a plant that’s very popular in Indonesian society because it contains anti-cancer substances. Nowadays, keladi tikus plants have been cultivated in tissue culture widely. The simplicia used in this study was keladi tikus from tissue culture which was separated into the upper part (leaves and petioles) and the bottom (tubers) dried in the sun. Dry simplicia was extracted with methanol at a temperature of 60-70 oC and the methanol extract was partitioned with ethylacetate then with n-BuOH solvents, and all extracts were tested for cytotoxic tests using the Brine Shrimp Lethality test (BSLT) method. The active fraction of ethylacetate extract, which is the tuber parts was carried out by column chromatography (SiO2; i). n-hexane: ethylacetate = 10: 1 ~ 1: 1; ethylacetate; MeOH; ii). n-hexane-ethylacetate = 5: 1) give one pure isolate. The results of identification based on Infrared (IR) spectra, and gas chromatography-mass spectra (GC-MS) are b-sitosterol which LC50 is 76.2 ppm